2023
DOI: 10.1101/2023.01.04.522820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corynebacterium of thediphtheriaecomplex in companion animals: clinical and microbiological characterization of 64 cases from France

Abstract: Objectives: Corynebacteria of the diphtheriae complex (Cdc) can cause diphtheria in humans and have been reported from companion animals. We aimed to describe animal infection cases caused by Cdc isolates. Methods: 18 308 animals (dogs, cats, horses and small mammals) with rhinitis, dermatitis, non-healing wounds and otitis were sampled in metropolitan France (August 2019 to August 2021). Data on symptoms, age, breed, and the administrative region of origin were collected. Cultured bacteria were analyzed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Based on epidemiologic studies and sequence homology, zoonotic transmission of C. ulcerans-type diphtheria between pigs and humans (Berger et al, 2013;Schuhegger et al, 2009) and between wild animals, dogs, and humans (Katsukawa et al, 2016) seems likely. Sporadically, C. ulcerans findings among game, hunting and pet dogs, cats and horses have been reported (Abbott et al, 2020;Carfora et al, 2018;Eisenberg et al, 2014;Katsukawa et al, 2016;Museux et al, 2023;Saeki et al, 2015;Zendri et al, 2021). During 2002-2008 most of the human C. ulcerans cases in France had had animal contact (dogs or cats) before infection, but animal-human transmission could not always be confirmed due to negative animal test results or lack of testing of animals (Bonmarin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Based on epidemiologic studies and sequence homology, zoonotic transmission of C. ulcerans-type diphtheria between pigs and humans (Berger et al, 2013;Schuhegger et al, 2009) and between wild animals, dogs, and humans (Katsukawa et al, 2016) seems likely. Sporadically, C. ulcerans findings among game, hunting and pet dogs, cats and horses have been reported (Abbott et al, 2020;Carfora et al, 2018;Eisenberg et al, 2014;Katsukawa et al, 2016;Museux et al, 2023;Saeki et al, 2015;Zendri et al, 2021). During 2002-2008 most of the human C. ulcerans cases in France had had animal contact (dogs or cats) before infection, but animal-human transmission could not always be confirmed due to negative animal test results or lack of testing of animals (Bonmarin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, infection is associated with mild respiratory and cutaneous manifestations with more serious manifestations thought to be linked to immunocompromise or inadequate vaccination (Gower et al, 2020). C. ulcerans has been isolated from many domesticated and wild animals (Eisenberg et al, 2015;Seto et al, 2008;Sting et al, 2023;Tejedor et al, 2000;Terriere et al, 2022;Thomas et al, 2022); the earliest reports of human infection were associated with the drinking of unpasteurised bovine products (Hacker et al, 2016), though companion animals such as cats and dogs are more frequently implicated in recent reports (Abbott et al, 2020;Carfora et al, 2018;Museux et al, 2023).…”
mentioning
confidence: 99%
“…Like in humans, the burden of C. ulcerans colonization or infection in animals is sparsely described. Several prevalence studies (of between 60 and 13,310 animals, Table 1) have indicated that the bacteria may be carried by 0.4%-29% of monkeys in closed breeding colonies (Hirai-Yuki et al, 2013;Panaitescu et al, 1977), 0.07%-7.2% of dogs in shelters, local government custody, or veterinary hospitals (Museux et al, 2023;Abbott et al, 2020;Dias et al, 2010;Katsukawa et al, 2012), and 6.25% of cats in veterinary hospitals (Abbott et al, 2020). One prevalence study in farm pigs found many Corynebacterium species, but not C. ulcerans (Boschert et al, 2014).…”
mentioning
confidence: 99%